(untitled) (CIPEEX, 2022)
THE CONSUMPTION OF COOKING OIL IS WIDELY USED IN FOOD PREPARATION IN CAFETERIAS, RESTAURANTS, HOMES ANDOTHERS. HOWEVER, MANY DO NOT KNOW WHERE AND HOW TO PROPERLY DISPOSE OF THIS MATERIAL, WHICH CANCAUSE SEVERAL SERIOUS PROBLEMS FOR THE ENVIRONMENT. BASED ON THESE QUESTIONS, PROG လLEO AIMS TO BEAN APPLICATION TO IDENTIFY CORRECT DISPOSAL STATIONS, REDUCING THE TIME SPENT FOR ITS EXECUTION.